2021
DOI: 10.3389/fphar.2021.598925
|View full text |Cite
|
Sign up to set email alerts
|

In silico Analyses of Immune System Protein Interactome Network, Single-Cell RNA Sequencing of Human Tissues, and Artificial Neural Networks Reveal Potential Therapeutic Targets for Drug Repurposing Against COVID-19

Abstract: Background: There is pressing urgency to identify therapeutic targets and drugs that allow treating COVID-19 patients effectively.Methods: We performed in silico analyses of immune system protein interactome network, single-cell RNA sequencing of human tissues, and artificial neural networks to reveal potential therapeutic targets for drug repurposing against COVID-19.Results: We screened 1,584 high-confidence immune system proteins in ACE2 and TMPRSS2 co-expressing cells, finding 25 potential therapeutic targ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 176 publications
(208 reference statements)
0
10
0
Order By: Relevance
“…Previous COVID-19 studies reported that hub-high traffic genes in the brown module, such as RBX1 ( 207 210 ), PSMA3 ( 211 ), PSMA6 ( 212 ), PTEN ( 213 ), VPS29 ( 214 , 215 ), SNRPE ( 216 ), PSMA4 ( 217 ), TXN ( 218 ), PTGES3 ( 219 , 220 ), RHOA ( 57 , 221 , 222 ), CANX ( 209 ), B2M ( 223 ), GDI2 ( 57 , 224 , 225 ), TXNL1 ( 226 ), SUMO1 ( 147 , 227 , 228 ), PSMC2 ( 229 ), REEP5 ( 230 ), DECR1 ( 108 ), RAB10 ( 224 ), PRDX3 ( 231 , 232 ), ACTR2 ( 215 ), TNFSF13B ( 192 , 233 , 234 ), and ARPC3 ( 215 ), have a central role in host-SARS-COV-2 interactions. For example, ARDS and ALI in patients with severe COVID-19 were directly associated with increased expression of the PTEN and RHOA hub-high traffic genes, respectively ( 213 , 222 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous COVID-19 studies reported that hub-high traffic genes in the brown module, such as RBX1 ( 207 210 ), PSMA3 ( 211 ), PSMA6 ( 212 ), PTEN ( 213 ), VPS29 ( 214 , 215 ), SNRPE ( 216 ), PSMA4 ( 217 ), TXN ( 218 ), PTGES3 ( 219 , 220 ), RHOA ( 57 , 221 , 222 ), CANX ( 209 ), B2M ( 223 ), GDI2 ( 57 , 224 , 225 ), TXNL1 ( 226 ), SUMO1 ( 147 , 227 , 228 ), PSMC2 ( 229 ), REEP5 ( 230 ), DECR1 ( 108 ), RAB10 ( 224 ), PRDX3 ( 231 , 232 ), ACTR2 ( 215 ), TNFSF13B ( 192 , 233 , 234 ), and ARPC3 ( 215 ), have a central role in host-SARS-COV-2 interactions. For example, ARDS and ALI in patients with severe COVID-19 were directly associated with increased expression of the PTEN and RHOA hub-high traffic genes, respectively ( 213 , 222 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the most essential protein interactions, a WH protein–protein interactome (WH-PPi) network was created by using the human proteome of the Cytoscape StringApp, taking into account zero node addition and the highest confidence interactions (cutoff = 0.9) related to experiments, databases, and co-expression 28 , 29 . The degree of centrality represents the number of edges the nodes have in a network 30 32 , and this centrality index was calculated using the CytoNCA app 33 . Nodes and edges were organized through the organic layout, and the WH-PPi network was visualized through the Cytoscape software v.3.7.1 34 .…”
Section: Methodsmentioning
confidence: 99%
“…In this situation, multi-target therapy could be used to provide a synergistic antiviral, immunomodulatory, and anti-inflammatory impact at the same time. Around 4000 clinical trials on COVID-19 have been conducted worldwide [ 297 ], employing small molecules as single or combination treatments with various antiviral medicines.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Furthermore, the computational docking results revealed that several known and newly synthesized chemical compounds had high inhibitory binding affinities with the docked SARS-CoV-2 proteins, suggesting that they could be useful lead compounds for the design and synthesis of new anti-COVID-19 agents [ 304 , 309 , 310 ]. A combination of in silico analysis of immune system protein interactome networks, single-cell RNA sequencing of human tissues, and artificial neural networks was undertaken in one of the recent (2021) studies to reveal potential therapeutic targets for drug repurposing against COVID-19 [ 297 ]. As a consequence, 47 approved drugs, 25 under-investigation compounds, and 50 experimental compounds with a strong affinity for 15 possible therapeutic targets were discovered and recommended for further research [ 297 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation